From Combating Religious Blasphemy to Promoting Peace: Reflections on the Role of Islamic Da’wah and Law in Indonesia's Pluralistic Society - Haq, Thoriqul; Mat Isa, Noor Aqsa Nabila (International Journal of Law and Society, 2024)
This study examines Da’wah's role in addressing the blasphemy issue in Indonesia and promoting peace in a pluralistic society. As a form of spreading Islamic teachings, Da’wah has a significant historical role in dealing with religious conflicts. This study aims to understand how Muslim leaders and communities use Da’wah to address blasphemy, reduce conflict, and build social harmony. With a qualitative approach, this study uses a descriptive-analytical method through analysis of historical documents, in-depth interviews with religious figures, and literature studies related to blasphemy cases. Data analysis techniques involve data reduction, data presentation, and inductive drawing of conclusions. The validity of the data is guaranteed through triangulation of data sources, namely comparing the results of interviews, documents, and relevant literature. The study results show that Da’wah is used through three main strategies: education to strengthen religious understanding, interfaith dialogue to build cross-faith communication, and a legal approach to handle blasphemy allegations formally. This strategy not only protects Islamic teachings but also strengthens social harmony. Da’wah also plays a vital role in enhancing the values ​​of tolerance, mediating conflict, and promoting peaceful life in a pluralistic Indonesian society. Da’wah is a tool for affirming Islamic identity and an effective instrument of social mediation. This finding contributes to the understanding of religious dynamics in Indonesia and its relevance in overcoming the challenges of interfaith relations in the era of globalization.